The attainment set of the φ-envelope and genericity properties - Cabot, A.; Jourani, A.; Thibault, L.; Zagrodny, D. (MATHEMATICA SCANDINAVICA, 2019)
The attainment set of the φ-envelope of a function at a given point is investigated. The inclusion of the attainment set of the φ-envelope of the closed convex hull of a function into the attainment set of the function is preserved in sufficiently general settings to encompass the case φ being a norm in a power not less than 1. The non-emptiness of the attainment set is guaranteed on generic subsets of a given space, in several fundamental cases.